PERAN DINAS TENAGA KERJA KOTA PEKANBARU DALAM MEMPERSIAPKAN TENAGA KERJA UNTUK PERSAINGAN MEA - Sufi, Wasiah (EDUTECH CONSULTANT, 2017)
Knowing the role of this research for the Department of Labor Employment Pekanbaru In Preparing For Competition MEA. Type Research Research type is descriptive qualitative research. The study was conducted at the Department of Labor Pekanbaru. The data collection is done by distributing questionnaires, interviews and documentation. Data analysis descriptive analysis of data collected after the coding is done, the next presentation and to classify them, and then the process of analysis and ends with a conclusion. The results showed that the Department of Labor's role in preparing the workforce for MEA competition is not optimal, is also in accordance with the results of questionnaires which researchers recapitulation proposed by the percentage of 63.12% of respondents disagree that Office. Labor Pekanbaru already optimal role in preparing the workforce for MEA competition.